2011
DOI: 10.1016/j.cell.2011.05.030
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Primary Cilium in Notch Signaling and Epidermal Differentiation during Skin Development

Abstract: SUMMARY Ciliogenesis precedes lineage-determining signaling in skin development. To understand why, we performed shRNA-mediated knockdown of seven intraflagellar-transport-proteins (IFTs), and conditional ablation of Ift-88 and Kif3a during embryogenesis. Both in cultured keratinocytes and embryonic epidermis, all eliminated cilia, and many (not Kif3a) caused hyperproliferation. Surprisingly and independent of proliferation, ciliary-mutants displayed defects in Notch-signaling and in commitment of progenitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
302
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(320 citation statements)
references
References 63 publications
11
302
4
3
Order By: Relevance
“…Two recent studies 64,65 have recently reported that impaired ciliogenesis impacts skin homeostasis and affects the pilosebaceous unit from which cylindroma are believed to originate. This convinced us that future studies designed to precisely characterize the molecular pathways regulated by CYLD during ciliogenesis might provide novel insights into how CYLD deregulation results in cylindroma in the cylindromatosis pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies 64,65 have recently reported that impaired ciliogenesis impacts skin homeostasis and affects the pilosebaceous unit from which cylindroma are believed to originate. This convinced us that future studies designed to precisely characterize the molecular pathways regulated by CYLD during ciliogenesis might provide novel insights into how CYLD deregulation results in cylindroma in the cylindromatosis pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the classifi cation of cancers is relatively direct, the understanding of the ontogenetic origin of cancer remains elusive. One reason is that every cancer is diff erent in terms of originating tissue, formation, and gene expression (Ezratty et al, 2011). It has been proposed that cancer initiates with a small number of "stem cells", that have the capacity to replenish the tumor in its entirety (Hill and Wu, 2009 (Chung et al, 2010) in solid tumors of the breast, colon, brain and other sites.…”
Section: Initiationmentioning
confidence: 99%
“…In mammals, canonical SHH signaling promotes localization of Smo to the primary cilium, a microtubule-based specialized cell surface protrusion, considered today a critical organizer for molecules involved in SHH signaling in vertebrates (Goetz et al, 2009, Ezratty et al, 2011. SHH ultimately exerts its eff ects by infl uencing the balance between GLI activator and repressor forms.…”
Section: The Shh/gli Pathway At a Glancementioning
confidence: 99%
“…Mounting evidence has indicated that the primary cilium houses a high density of signaling molecules and functions as a center to orchestrate a diverse number of signaling pathways important for development or tissue homeostasis (Dorn et al, 2012;Ezratty et al, 2011;Goetz and Anderson, 2010;Lancaster et al, 2011;Oh and Katsanis, 2012). The primary cilium represents the 'cell antenna', and is sensitive to changes in extracellular cues (Barr and Sternberg, 1999;Nauli et al, 2003;Praetorius and Spring, 2005;Singla and Reiter, 2006;Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%